2005
DOI: 10.1097/01.qai.0000159516.39982.1b
|View full text |Cite
|
Sign up to set email alerts
|

Management of HIV-1 Infection With a Combination of Nevirapine, Stavudine, and Lamivudine

Abstract: The overall results within the 12-month treatment period indicated an effective suppression of viral replication, the reconstitution of the immune system, and improvement of the physical well-being of the study population. Though there may be differences in global distribution of the infecting HIV-1 subtypes, the clinical and biologic results of this study compared favorably to those documented in cohorts treated with branded and generic ARV drugs in some developed and developing countries. The cumulative data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 19 publications
2
48
0
Order By: Relevance
“…These findings were similar to those of studies [6,7] conducted in resourcelimited settings. Adherence, injecting drug use, and baseline pVL were associated with time to viral load suppression in multivariate analysis; these observations have also been previously reported [6,[8][9][10][11][12][13]. These data indicate that this regimen should be expected to lead to successful virological suppression in most settings, and, if this is not the case, it may indicate serious flaws with the implementation of antiviral programmes.…”
Section: Discussionsupporting
confidence: 82%
“…These findings were similar to those of studies [6,7] conducted in resourcelimited settings. Adherence, injecting drug use, and baseline pVL were associated with time to viral load suppression in multivariate analysis; these observations have also been previously reported [6,[8][9][10][11][12][13]. These data indicate that this regimen should be expected to lead to successful virological suppression in most settings, and, if this is not the case, it may indicate serious flaws with the implementation of antiviral programmes.…”
Section: Discussionsupporting
confidence: 82%
“…Numerous studies have demonstrated high levels of adherence among persons receiving ART in resource-limited areas [14,[22][23][24][25], including among African cohorts. A recent systematic overview found that 77% of sub-Saharan Africans maintained 100% adherence with ART, compared with 55% of North Americans [8].Therefore, the ADAR study results regarding adherence in a Tanzanian population are consistent with observations from other cohorts in resource-limited areas.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial rates of decline in the number of opportunistic infections and in the prevalence of AIDS-related mortality have been observed [12,13]. A number of studies have reported reductions in the level of plasma HIV-1 RNA and increases in the number of the CD4 cell count, even among PLWHA with very low initial CD4 counts [14][15][16][17][18]. Antiretroviral drugs must be taken as a lifelong therapy and their success relies on continual adherence to the medication regimen.…”
Section: Introductionmentioning
confidence: 99%